The examination of the relationship between internet addiction and perceived stress in terms of perceived social support - Kavaklı, Mehmet; Yalçın, Süleyman Barbaros (Journal of Dependence, 2019)
Objective: The purpose of this study was to investigate the relationship between internet addiction and perceived stress in terms of perceived social support.Method: The sample was composed of 346 university students studying at Necmettin Erbakan University. Data was gathered by using personal information form, the Multidimensional Scale of Perceived Social Support, the Perceived Stress Scale and Internet Addiction Scale.Results: Predictive relationships among variables were examined with the structural equation modelling. The results showed that internet addiction positively predicts perceived stress. Furthermore, it is determined that there is a significantly and negatively relationship between internet addiction and perceived social support. It is found that there is also a negative relationship between perceived social support and perceived stress. Besides, it is found out that perceived social support mediates in the relationship between internet addiction and perceived stress levels.Conclusion: Internet addiction predicts participants’ perceived stress levels and perceived social support has a mediating role in the relationship between internet addiction and perceived stress. This result shows the importance of perceived social support.
Keywords: Internet addiction; perceived stress; perceived social support